Deletion of calcineurin from GFAP‐expressing astrocytes impairs excitability of cerebellar and hippocampal neurons through astroglial Na+/K+ ATPase. Issue 3 (18th October 2019) - Tapella, Laura; Soda, Teresa; Mapelli, Lisa; Bortolotto, Valeria; Bondi, Heather; Ruffinatti, Federico A.; Dematteis, Giulia; Stevano, Alessio; Dionisi, Marianna; Ummarino, Simone; Di Ruscio, Annalisa; Distasi, Carla; et al.
Abstract: Astrocytes perform important housekeeping functions in the nervous system including maintenance of adequate neuronal excitability, although the regulatory mechanisms are currently poorly understood. The astrocytic Ca 2+ /calmodulin‐activated phosphatase calcineurin (CaN) is implicated in the development of reactive gliosis and neuroinflammation, but its roles, including the control of neuronal excitability, in healthy brain is unknown. We have generated a mouse line with conditional knockout (KO) of CaN B1 (CaNB1) in glial fibrillary acidic protein‐expressing astrocytes (a stroglial c alcin eurin KO [ACN‐KO]). Here, we report that postnatal and astrocyte‐specific ablation of CaNB1 did not alter normal growth and development as well as adult neurogenesis. Yet, we found that specific deletion of astrocytic CaN selectively impairs intrinsic neuronal excitability in hippocampal CA1 pyramidal neurons and cerebellar granule cells (CGCs). This impairment was associated with a decrease in after hyperpolarization in CGC, while passive properties were unchanged, suggesting impairment of K + homeostasis. Indeed, blockade of Na + /K + ‐ATPase (NKA) with ouabain phenocopied the electrophysiological alterations observed in ACN‐KO CGCs. In addition, NKA activity was significantly lower in cerebellar and hippocampal lysates and in pure astrocytic cultures from ACN‐KO mice. While no changes were found in protein levels, NKA activity was inhibited by the specific CaN inhibitor FK506 in both cerebellar lysates and primary astroglia from control mice, suggesting that CaN directly modulates NKA activity and in this manner controls neuronal excitability. In summary, our data provide formal evidence for the notion that astroglia is fundamental for controlling basic neuronal functions and place CaN center‐stage as an astrocytic Ca 2+ ‐sensitive switch. Main points: A mouse model with astrocyte‐specific deletion of calcineurin (ACN‐KO) does not show alterations in neurodevelopment and may be used for investigating brain physiology. In 1 mo old ACN‐KO mice, intrinsic neuronal excitability is impaired due to specific inhibition of astroglial Na + /K + ATPase.